AI-Driven Dynamics: ChatGPT Transforming ELT Teacher-Student Interactions - FX. Risang Baskara (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2023)
In the rapidly evolving educational domain, where artificial intelligence (AI) is pivotal, English Language Teaching (ELT) witnesses profound transformations. This study, focusing on integrating ChatGPT, an AI-driven language model, illuminates its substantial impact on the dynamics between teachers and students within ELT. Pertinent to this research is the inquiry into how ChatGPT reshapes teacher roles, responsibilities, and pedagogical practices, an area previously overlooked in the realm of AI in education. Employing a theoretical lens, the study scrutinises active learning models, technology integration theories, and paradigms of teacher professional development. Such analysis is crucial in comprehending teachers' shift from traditional methodologies to more facilitative and supportive roles, emphasising the urgency of this investigation for active learning's progression. Utilising diverse analytical approaches, ChatGPT propels pedagogies encouraging active learning, notably blended, collaborative, and project-based learning, while accentuating the necessity of professional development and institutional support for teachers' successful transition to these novel roles. These findings offer pivotal insights for the higher education sector, underlining the imperative of embracing AI's transformative potential, particularly tools like ChatGPT. By delving into ChatGPT's influence on teacher-student interaction and pedagogical methods, the study carves a significant path for future exploration and application in technology-enhanced ELT.